Análise temporal e predição dos acidentes escorpiônicos das macrorregiões do estado de São Paulo - Brasil - SANTELLO, SAMARA BERTIN SUGUITANI (2024)
Scorpionism is the main occurrence caused by venomous animals in Brazil; from the neglected tropical diseases it is the one which presents the most increasing number of notifications. Since 1993, its notification is mandatory through the Notifiable Diseases Information System (SINAN). São Paulo state, located in the southeast region of Brazil, is included in this growing number of notified cases. In 2022, it was the state that showed the most increasing number of notified cases in Brazil. The most frequent kinds of scorpion in São Paulo state are Tityus serrulatus and Tityus bahiensis; as the Tityus serrulatus species, they predominate in urban areas, and its venom may cause severe poisoning, representing a serious public health issue, especially to children. The objective of the study was to determine the temporal distribution of scorpionism in the seventeen macroregions of São Paulo estate - Brazil, and make predictions about future cases, and also to correlate health regions to with the greater number of notifications in the state. Allowing to direct actions to the regions which most need reinforcements, both in the victim care sector and in the preventive sector. Data were collected from the Notifiable Diseases Information System (SINAN), it was decided to start in the year 2013, for the data being more consistent from this period on. Annual incidence rates of scorpionic occurrences were calculated to for every 100,000 inhabitants to the seventeen health macroregions. ARIMA and SARIMA autoregressive models were used, with favorable results to some regions, being possible to determine seasonality, as well as to predict the non-stationarity of cases in the years 2023, 2024 e 2025 in the health regions of Barretos, Franca, Piracicaba, Registro, São João da Boa Vista and Sorocaba. The regions with the highest number of notifications in the state, comparing years 2013 and 2022, remained within the same macroregions, which are in descending order: Registro, the one with the highest number of reported cases, followed by Presidente Prudente, Piracicaba, Ribeirão Preto, São João da Boa Vista, Marília and São José do Rio Preto, and it highlighted the need for public policies and intervention target at these regions, which up to the present moment has no effective measures and no expectations of controlling this plague.